Smooth transition from grid to standalone solar diesel mode hybrid generation system with a battery - Elsherbiny, Aya M; Nada, Adel S.; Ahmed, Mohammed Kamal (Institute of Advanced Engineering and Science, 2019)
This paper described a self-supply smart microgrid which may be a low voltage or medium voltage distribution network. It considered an efficient energy system in which different renewable sources as photo-voltaic array, wind, or conventional as diesel generator, and storage called distributed generators which organized to chance the load power demand at any time with reliability. It can operate either on-grid or off-grid configuration, especially limited areas far from the utility grid needed another backup power. By using Matlab/Simulink, a solar PV system is modeled, simulated, and determined the characteristic of a particular photovoltaic cell panel under the influence of different values of ambient conditions. Taking into consideration MPPT algorithm which increases the solar energy efficiency by Incremental conductance technique to track MPP correctly with fast response. Power electronic DC/DC converter and DC/AC inverter are used with PWM technique. To compensate the power fluctuations of the system under different possible transient cases, a high performance control based on an improved virtual synchronous generator is added to confirm smooth variants in voltage, frequency and active power during transient conditions. The results show the PV/Diesel generator/battery/power/frequency and voltage performance at two different conditions.